Chirality Induced Spin Selectivity – the Photoelectron View. Issue 11 (21st November 2022) - Möllers, Paul V.; Göhler, Benjamin; Zacharias, Helmut
Abstract: In this short overview we discuss the manifestation of the chirality‐induced spin selectivity (CISS) effect in photoelectron spectroscopy experiments with direct spin analysis. Various systems, from the initially investigated monolayers of molecular biosystems and organic hepta‐helicene to recent chirally grown solid oxide films, are evaluated. High spin polarization values of up to P=60 % have been observed for samples at room temperature. For all classes it was shown that the longitudinal spin orientation changes sign with a change of the enantiomeric form. Recent advances allow to distinguish the contributions of electrons with different kinetic energies to the electron spin polarization, and thus to distinguish the CISS effect from bulk contributions to the spin originating from different mechanisms. Abstract :